EFFECTIVE WAYS OF THE REFINING-MODIFYING PROCESSING OF HYPEREUTECTIC SILUMINS - S. P. Korolev; S. P. Zadrutski; B. M. Nemenenok; V. M. Mihailovski; A. G. Sheshko; M. I. Aniskovich (Литьë и металлургия, 2006)
New effective preparation for modifying of hypereutectic silumins AK18 — piston alloy is created on the basis of research-experimental-industrial works.